Influence of controlled atmosphere storage on polyphenoloxidase activity in relation to colour changes of minimally processed ‘Jonagored’ apple - Rocha, A. M. C. N. (2011)
The effects of the storage atmosphere composition (2% O2 + 4% CO2; 2% O2 + 8% CO2; 2% O2 + 12% CO2) on polyphenoloxidase activity and phenolic content of the ‘Jonagored’ apple variety during cold storage was evaluated, and the relationship with enzymatic browning investigated. Controlled atmosphere storage inhibited the polyphenoloxidase (PPO) activity of apple cubes during storage. It seems that the higher the concentration of carbon dioxide in the storage atmosphere the higher inhibition of PPO and the lower browning achieved. At the substrate-enzyme levels investigated, the phenolic content, substrate level was the major factor determining darkening.